TECHNOLOGY ADVANCEMENTS TO ENHANCE FUTURE ENGLISH LANGUAGE INSTRUCTORS’ COMMUNICATION CULTURES - Zulfizar Xatamovna Irgasheva (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The importance of effective communication in language instruction is emphasized in this article, which examines methods for improving the communication culture among aspiring English language instructors. It looks at the current issues with teachers’ communication skills and suggests a framework that includes technology integration, reflective practice, and collaborative learning. The study intends to give aspiring teachers the skills they need to interact with a variety of student populations by creating a welcoming atmosphere that promotes candid communication and cross-cultural understanding. The results emphasize how crucial communication is to enhancing pedagogical proficiency and raising overall language acquisition results for students. By offering practical advice to curriculum designers and teacher trainers, this study adds to the continuing conversation about teacher education.